1905
DOI: 10.1007/bf02445272
|View full text |Cite
|
Sign up to set email alerts
|

Geschlechts-Krankheiten

Abstract: ammoniakalische Reaktion des Harns bei Phosphaturie, sowie fiber Phosphaturie und Ammoniurie als objektive Symptome der Neurasthenie. Deutsche reed. Wechenschr. Nr. 38. 17. Sept. 1903.Von der Regel ausgehend, daft eine ausgesprochene ammoniakalische Harnreaktion stets yon in den Urin ge]angten Bakterien hervorgerufen set, land Freudenberg eine Ausnahme in der Phosphaturie. Hier waren keine Bakterien vorhanden~ das Ammoniak mul~te also im K6rper selbst gebildet worden seth. Verf. unterscheidet 3 Grade der Phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1920
1920
1920
1920

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In addition to occasional instances of animals showing generalized lesions, there were other facts, however, which indicated that the infecting organism itself was not confined to the region of inoculation. As has been mentioned, Ossola (12) and Truffi (11) demonstrated the presence of spirochetes in the inguinal lymph nodes of rabbits inoculated in the scrotum in 1909, and as early as 1908, Neisser (13) reported successful inoculations of monkeys with material from the spleen and bone marrow of three out of seven rabbits killed 7 to 8 weeks after inoculation with a spleen-bone marrow emulsion from monkeys. These rabbits had been inoculated in the testicles, and although no local lesions had been detected up to the time they were killed, it was claimed that the virus was recovered from the internal organs.…”
mentioning
confidence: 88%
“…In addition to occasional instances of animals showing generalized lesions, there were other facts, however, which indicated that the infecting organism itself was not confined to the region of inoculation. As has been mentioned, Ossola (12) and Truffi (11) demonstrated the presence of spirochetes in the inguinal lymph nodes of rabbits inoculated in the scrotum in 1909, and as early as 1908, Neisser (13) reported successful inoculations of monkeys with material from the spleen and bone marrow of three out of seven rabbits killed 7 to 8 weeks after inoculation with a spleen-bone marrow emulsion from monkeys. These rabbits had been inoculated in the testicles, and although no local lesions had been detected up to the time they were killed, it was claimed that the virus was recovered from the internal organs.…”
mentioning
confidence: 88%